VARIASI GENETIK LOCI STR CODIS (THO1,TPOX) MANUSIA GILIMANUK (PULAU BALI) - Koesbardiati, Toetik; Yudianto, Ahmad; Murti, Delta Bayu; Suriyanto, Rusyad Adi (Berkala Arkeologi, 2013)
It is assumed that Mongoloidâ€™s migration came from western and northern part of Indonesia in various waves of migration. The migrant population then mixed with initial inhabitants, which are Australomelanesoid. The wave of migration moved further to the eastern Indonesia and mixed with migrant that entered from east (Papua). Some researches show that the concentration of mixture (hybridization) of migration was around Wallaceâ€™s line. Gilimanuk is one of prehistoric site that yields Neolithic human remains. It is assumed that Gilimanuk can give worthy information about human variation at that time. The aim of the research is to describe the human genetic variation at site of Gilimanuk. The material is DNA (deoxyribonucleic acid) has been extracted from many piece of bone of Gilimanukâ€™s human remains. We used STR (short tandem repeat) two loci (THO1 and TPOX) to gain human genetic variation. The result show all of sampleÂ yields band with different allele. This evidence confirms that they have a genetic affinity is not the same, or their genes from several population.